El derecho y el silencio - Rivera Ramos, Efrén (2017)
This essay explores the different dimensions of the relationship between law and silence. It proposes four lines of research: (1) silence as an object of regulation; (2) silence as a hermeneutical reference; (3) the social effects of the silences of law, and (4) silence as constitutive of law. The topic of silence as an object of regulation is divided, in turn, into four categories: (a) compelled silence; (b) the right to silence; (c) legal protection against silence; and (d) the attribution of legal consequences to silence. The second line of research looks into the role of silence in legal interpretation. More concretely: What is the legal meaning of not saying? What normative consequences can or must interpreters draw from the law´s silence? Thirdly, the essay examines some of the social effects of silences in the law, such as the generation of invisibility, absences, marginalization, exclusion and relations of subordination and domination. Fourthly, the author proposes that silence is a constitutive element of law, to the extent that law operates quietly to produce and reproduce the world in which we live. The essay concludes with an exhortation to convert silence into a category of legal analysis, so that it is routinely incorporated into our teaching, research, publications and legal practice.